Toxicity assessment and anti-inflammatory effects of male papaya flower extract - Nguyen , Hồng Sơn; Doan , Xuân Tuyền; Tran, Huyền Trân (Tạp Chí Khoa Học Và Công Nghệ Trường Đại Học Bình Dương, 2024)
Male papaya flower is a medicinal herb used in traditional medicine to treat cough symptoms. Male papaya flower was extracted using the maceration method (96% ethanol solvent). The safety of male Papaya flower extract was tested on male mice who received the highest dose drawn through a needle, with mortality and toxicity monitored for 72 hours. The extract's cough-reducing effect was tested on an acute cough model in a 1 liter closed bottle containing 25% amoniac. Mice were given male papaya flower extract at doses of 3.6 g/kg and 1.8 g/kg for three days, with Neo-codion® 1 tablet/kg serving as a positive control. On the third day, one hour after administration, induce cough and assess the number of latent cough periods, cough counts, and cough inhibition ability. The result show that male papaya flower extract was safely administered to mice at a Dmax dose of 18 g/kg. In the acute cough model, doses of 3.6 g/kg and 1.8 g/kg both reduced the number of coughs by a statistically significant amount compared to the control group.